Spontaneous polarization in the cluster ferroelectric system close to the phase transition point - Korynevskii, N.A. (Condensed Matter Physics, 1999)
A two-stage layer by layer integration of the ferroelectric two-particle cluster
system partition function functional is made in the quartic basic distribution
of the dipole momentum ﬂuctuation approximation. The shape of the layers
of integration is determined by peculiarities of ﬂuctuation processes (of the
Gaussian and the non-Gaussian types) for separate subsets of collective
variables. The minimization procedure of the partition function functional
unintegrated over one variable (with quasimomentum and Matsubara's frequency equal to zero) gives an equation for the order parameter (i.e., the
spontaneous polarization) of the system. Solutions of this equation at various values of system parameters and external ﬁeld are found in the Tc
neighbourhood. В наближенні четвірного базисного розподілу фаз флуктуацій дипольного моменту сегнетоелектричної двочастинкової кластерної
системи виконано двоетапне пошарове інтегрування функціонала
статистичної суми. Форма шарів інтегрування визначається особливостями флуктуаційних процесів (гаусового і негаусового типу) окремих підмножин колективних змінних. Мінімізація недоінтегрованого за однією змінною (яка характеризується нульовими значеннями квазіімпульса і мацубарівської частоти) функціонала статистичної
суми визначає рівняння для параметра порядку (спонтанної поляризації) системи. Знайдено розв’язки цього рівняння при різних значеннях температури (в околі Tc ), параметрів системи і зовнішнього
поля.